Electro-acupuncture for Facial Palsy with Synkinesis - YOSHIDA, Motoaki; SAKAI, Tomomi; KIMURA, Satomi; OKADA, Tomihiro (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 2005)
[Objective] For one facial palsy subject with synkinesis, we applied asynchronous 100Hz EAT and examined the effects. We also examined changes in the effects according to various frequencies. [Methods] We applied EAT to Mm.faciales, and the evaluation was based mainly on EMG findings (the EMG amplitude, EMG survival continuance time) as well as facial palsy score, VAS, ENoG. We examined changes after treatment and observed the process. [Results] Change in EMG amplitude were not recognized, but the EMG persistance was shortened after treatment and during the process of observation. VAS, facial palsy score, and ENoG were improved. EMG persistance was not changed by 1 Hz EAT, was prolonged by 30Hz EAT, and was shortened by 100 Hz EAT. [Conclusion] One hundred Hz EAT shortened EMG persistance, and reduced the subjective symptoms of synkinesis. In addition, we were able to improve facial palsy score and ENoG value.